Fingerprint Acquisition: Fingerprint Acquisition Based on Photo‐Thermal Coloration of MoO3 Ceramic upon the Irradiation of Multiband Light outside the Bandgap (Adv. Mater. Technol. 11/2020). Issue 11 (10th November 2020) - Li, Mingjun; Yang, Zhengwen; Wen, Yugeng; Ruan, Jiufeng; Ren, Youtao; Qiu, Jianbei; Song, Zhiguo; Wang, Yuehui; Liu, Bitao
Abstract : In article number 2000562, Zhengwen Yang, Bitao Liu, and co‐workers present a method of fingerprint acquisition, obtained by means of the photo‐thermal‐chromism of MoO3 photochromism ceramic upon irradiation of multiband light outside the bandgap, which breaks the limitation of photochromism caused by monochromatic wavelength inside the band gap. The acquisition fingerprint based on the photochromism of MoO3 ceramic exhibits excellent repeatability, high reproducibility and long preservation persistence under heat‐treatment.